Modular Distance Learning: Perceived Challenges and Strategies of Secondary Science Teachers in Mandaon District, Masbate, Philippines - Cajurao, Erdee C; Mortel, John Carlo V.; Maglente, Maria Shiela C.; Dumaguin, Jeralin R.; Paloma, Virgie V.; Rios, Calyn R.; Rivas, Mark Alvin D. (Future Science / FSH-PH Publications, 2023)
This study aimed to examine the challenges encountered by science teachers in implementing modular distance learning and the coping strategies they employed to address these challenges. Using a mixed-method research approach, data were collected through a survey of thirty-eight Junior High School science teachers in Mandaon District in Masbate, Philippines. Findings revealed that the implementation of modular distance learning presented various challenges, including technical problems, distribution and retrieval difficulties, student utilization issues, and unreliable assessment results. To cope with these challenges, teachers employed various strategies, including attending ICT training, asking for technical assistance, developing income-generating projects, and utilizing differentiated instruction and targeted assessments. The study also highlights the need for more parental involvement, adequate funding for schools, clear instructions and guidance to students, and proper monitoring of student performance. Overall, the study suggests that with effective implementation and support, modular distance learning can be an effective mode of instruction, particularly during times of crisis.